Coronary Embolism despite CHA₂DS₂-VASc Score of Zero: Should We Reconsider Anticoagulation?. (31st July 2021) - Ahmed, Ammar; Assaf, Andrew; Shankar, Aditi; Zughaib, Marcel
Abstract : Coronary embolism (CE) is a rare but important cause of acute coronary syndrome. The most common source of emboli is considered to be infective endocarditis and atrial fibrillation. Various studies have estimated the prevalence of coronary embolism; however, diagnosis is challenging. Often, it is difficult to differentiate. Nonetheless, this is an important step as treating the underlying cause of an embolism is essential to limit recurrence. However, while this condition may have fatal consequences, due to its uncommon occurrence, there is no consensus on diagnosis and management. We present a case of a 53-year-old obese male, with a history of paroxysmal atrial fibrillation not on anticoagulation due to a low CHA2 DS2 -VASc score, who presented with chest pain associated with lightheadedness. ECG on admission revealed coarse atrial fibrillation, and troponin was gradually elevating on serial lab workup. Coronary angiography revealed a distal left anterior descending artery occlusion with apical wall akinesis without any evidence of atherosclerotic coronary artery disease. A presumptive diagnosis of coronary embolism secondary to paroxysmal atrial fibrillation was made, and the patient was started on anticoagulation despite a low CHA2 DS2 -VASc score. This case not only highlights coronary embolism but also illustrates that a low CHA2 DS2 -VASc score does not mean there is no risk of emboli. For such patients, it is important to take clinical reasoning into account along with the CHA2 DS2 -VASc score to determine the benefit of anticoagulation.